2016
DOI: 10.1016/j.pec.2016.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Biobehavioral determinants of glycemic control in type 2 diabetes: A systematic review and meta-analysis

Abstract: Objectives To conduct a model-driven meta-analysis of correlational research on psychological and motivational predictors of diabetes outcomes, with adherence factors as mediators. Methods A comprehensive literature search of published and unpublished studies located a sample of 775 individual correlational or predictive studies reported across 739 research reports. Results Results varied according to the outcome variable included in the regression models. Depression had a larger negative effect on adheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 23 publications
2
62
1
8
Order By: Relevance
“…Based on the common ground hypothesis, several biological mechanisms have been associated with poor diabetes outcomes in people with diabetes and depression [31][32][33][34][35][36][37]. This hypothesis assumes that diabetes and depression have common denominators, including genetic factors, overactivation of the innate immune system or dysregulation of the HPA axis.…”
Section: Mechanisms Linking Depression and Diabetesmentioning
confidence: 99%
“…Based on the common ground hypothesis, several biological mechanisms have been associated with poor diabetes outcomes in people with diabetes and depression [31][32][33][34][35][36][37]. This hypothesis assumes that diabetes and depression have common denominators, including genetic factors, overactivation of the innate immune system or dysregulation of the HPA axis.…”
Section: Mechanisms Linking Depression and Diabetesmentioning
confidence: 99%
“…Latinos with diabetes have lower levels of glycemic control than non-Hispanic Whites (11) and they are twice as likely to be hospitalized for diabetes related complications (12). Compared to their non-Latino White counterparts with diabetes, they also have higher rates of emotional distress (13,14) and although data vary by sampling strategy and the specific sub-ethnicity under investigation, Latinos as a group have been shown to have lower levels of the diabetes self-care behaviors (15,16) that are powerful determinants of glucose control (17). …”
Section: Introductionmentioning
confidence: 99%
“…For comparison, oral medications are expected to improve HbA 1c by ~11 mmol/mol (1.0%) . A recent systematic review of the behavioural determinants of good glycaemic control found that dietary adherence was the most important determinate (the other behavioural factors included were adherence to physical activity, medications, glucose self‐monitoring and appointment keeping).…”
Section: What Can Diet and Physical Activity Achieve?mentioning
confidence: 99%